1994
DOI: 10.1080/01431169408954320
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring change in the extent of salt-affected soils in northern India

Abstract: A large area of barren salt-affected soils has been reclaimed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…In the 1960s and early 1970s, the mapping and monitoring of SAS for categorization were performed at the local and regional scales for assessment of extent and spatial distribution (Hilwig and Karale, 1973; Iyer et al, 1975). Visual interpretation techniques developed using aerial photography were extended to satellite multi‐spectral data for delineating and mapping of SAS at the regional and national scales (Hilwig, 1980; Karale et al, 1983; Manchanda and Iyer, 1983; Singh, 1994a). The appearance of SAS with salt encrustation at the surface is generally smoother than normal soil surfaces and has higher reflectance in the visible and near‐infrared bands (Singh and Sirohi, 1994; Rao et al, 1995).…”
Section: Delineation Of Salt‐affected Soils In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1960s and early 1970s, the mapping and monitoring of SAS for categorization were performed at the local and regional scales for assessment of extent and spatial distribution (Hilwig and Karale, 1973; Iyer et al, 1975). Visual interpretation techniques developed using aerial photography were extended to satellite multi‐spectral data for delineating and mapping of SAS at the regional and national scales (Hilwig, 1980; Karale et al, 1983; Manchanda and Iyer, 1983; Singh, 1994a). The appearance of SAS with salt encrustation at the surface is generally smoother than normal soil surfaces and has higher reflectance in the visible and near‐infrared bands (Singh and Sirohi, 1994; Rao et al, 1995).…”
Section: Delineation Of Salt‐affected Soils In Indiamentioning
confidence: 99%
“…Subsequently, MSS data enabled delineation, mapping, and monitoring of SAS in the Indo‐Gangetic alluvial plains (Venkataranam, 1983; Sharma and Bhargava, 1988; Singh and Dwivedi, 1989; Dwivedi, 1996; Dwivedi and Sreenivas, 1998a; Manchanda et al, 2002), in the arid region (Kalra and Joshi, 1996), and in the coastal plains of Saurashtra (Joshi and Sahai, 1993). Multi‐spectral and multi‐date data of Landsat‐TM and ETM+ were processed visually or digitally for mapping of SAS over different parts of the country (Saha et al, 1990; Rao et al, 1991; Raina et al, 1991; Dwivedi, 1992; Singh, 1994a; Verma et al, 1994; Goyal et al, 1995; Dwivedi et al, 1999; Sujatha et al, 2000; IDNP, 2002). Apart from the normal combination of band‐2 (0.52–0.60 μm), band‐3 (0.63–0.69 μm), and band‐4 (0.76–0.90 μm) for FCC, a new three‐band best combination from Landsat‐TM data—band‐1 (0.45–0.52 μm), band‐3 (0.63–0.69 μm), and band‐5 (1.55–1.75 μm)—was identified on the basis of information content for characterizing SAS in the IGP (Dwivedi and Rao, 1992; Csillag et al, 1993).…”
Section: Delineation Of Salt‐affected Soils In Indiamentioning
confidence: 99%
“…Over the years, there have been many studies conducted on the use of microwave remote sensing for soil moisture estimation in various regions of the world (Ijjas & Rao, 1992). In India, most of the studies have focused on understanding the behaviour of soil moisture in relation to agricultural plot studies (Mohan et al, 1994;Rao et al, 1987;Singh, 1994) and, thus, there appears to be lack of reported work on soil moisture assessment by microwave remote sensing that is directed towards its utility for hydrological studies. In particular, northern India has a vast network of rivers and canals, and, therefore, spatial and temporal distribution of soil moisture in this region has a significant bearing on understanding the hydrological processes in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Se constató que la recuperación de suelos salinizados en el periodo 1956-1986 fue de un 22 %, mientras que la ex-tensión de la salinidad en la periferia de los bloques fue de 3 % [6]. En 1992, identificaron que la mejor combinación de tres bandas entre las 20 del Landsat Thematic Mapper (TM) para delimitar los suelos afectados por la salinidad en la planicie aluvial Indo-Gangetic fueron las bandas 1, 3 y 5 las que presentaron la mejor combinación [7]. En 1992, prepararon mapas de las áreas costeras del estado de Gujartat, India, que proveen información sobre la extensión e intensidad de las tierras afectadas por la salinidad, usando imágenes MSS Landsat-2, 1972 (multiespectral scanner) de 80 m de resolución espacial e imágenes TM Landsat-5, 1986.…”
unclassified